The Association Between Auditors' Fees and Earnings Management in New Zealand - Ananthanarayanan, Umapathy (Auckland University of Technology, 2008)
This study provides evidence between auditors' fees and earnings management in New Zealand. The fee measures used in this study are audit fees, non-audit fees and total fees paid by a client to the audit firm. For each of the three fee measures, I derive client importance fee measures that reflect a client’s economic importance to the auditor relative to other clients of the auditor at the city office and national levels. This study employs both performance adjusted discretionary accruals and current accruals as proxies for earnings management. Using a sample of 224 firm-years comprising firms listed on the New Zealand Stock Exchange (NZX) in fiscal years 2004 and 2005, the results of multivariate tests indicate an adverse association between non-audit fees and earnings management. In other words, non-audit fees paid by a client relative to fees paid by other clients, at the office and national levels, appear to impair the auditor’s independence because clients generating relatively more non-audit fees report greater discretionary and current accruals. Such evidence is more pronounced for income increasing accrual proxies for earnings management. The results also show that audit fee is not related to earnings management. As the results in this study are consistent across both discretionary and current accruals, the validity of the results is strengthened. This study contributes to the literature by providing insight into how auditors’ fee metrics indicating client importance affect earnings management in a legal and institutional environment of a small economy, and where the audit market is largely saturated with little room for growth. This study raises implications for relevant regulatory bodies in New Zealand pertaining to future developments of auditor independence and financial reporting regulations.
Keywords: Audit independence; Non-audit fees; Client importance; Discretionary and current accruals